2005
DOI: 10.1111/j.1537-2995.2005.04400.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro photochemical inactivation of cell‐associated human T‐cell leukemia virus Type I and II in human platelet concentrates and plasma by use of amotosalen

Abstract: In human plasma or PLT concentrates, the retroviruses HTLV-I and -II were strongly sensitive to the PCT with 150 micromol per L amotosalen (S-59) and a 3.0 J per cm2 UVA dose. This high efficiency for photoinactivation of these retroviruses opens a possibility of improving the safety of PLTs or plasma transfusion in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These studies showed that PCT with amotosalen and UVA light is effective against a broad range of pathogens in plasma. This finding is not surprising based on the pathogen inactivation efficacy previously demonstrated for PLTs with the same dose of amotosalen and same dose of UVA light 15‐20 . The levels of inactivation for representative viruses, bacteria, and protozoa were measured with PCT conditions developed for the commercial application of FFP.…”
Section: Discussionsupporting
confidence: 54%
“…These studies showed that PCT with amotosalen and UVA light is effective against a broad range of pathogens in plasma. This finding is not surprising based on the pathogen inactivation efficacy previously demonstrated for PLTs with the same dose of amotosalen and same dose of UVA light 15‐20 . The levels of inactivation for representative viruses, bacteria, and protozoa were measured with PCT conditions developed for the commercial application of FFP.…”
Section: Discussionsupporting
confidence: 54%
“…A photochemical treatment (PCT) system with amotosalen and ultraviolet (UV) A light pathogen inactivation of single‐donor plasma has been developed. In vitro studies of this PCT system have demonstrated broad‐spectrum inactivation of viruses, bacteria, protozoa, and contaminating donor WBCs 15‐17 . Retention of coagulation factor activity, antithrombotic proteins (protein C, protein S, and antithrombin III), and VWF‐CP activity has been demonstrated in plasma treated with this process (PCT plasma) 18,19 .…”
mentioning
confidence: 99%
“…In vitro studies of this PCT system have demonstrated broad-spectrum inactivation of viruses, bacteria, protozoa, and contaminating donor WBCs. [15][16][17] Retention of coagulation factor activity, antithrombotic proteins (protein C, protein S, and antithrombin III), and VWF-CP activity has been demonstrated in plasma treated with this process (PCT plasma). 18,19 PCT plasma also can be processed into PCT CSP, 20 or cryoprecipitate, 21 with a similar coagulation profile to conventional products.…”
mentioning
confidence: 99%
“…The inactivation mechanism combines the nucleic acid-intercalating property of amotosalen with its cross-linking capabilities after UVA activation to eliminate the replicative function of treated pathogens. PCT has been shown to inactivate a broad spectrum of viruses, bacteria, parasites, and white blood cells and create safer blood-transfusion products [11,12,[14][15][16][17][18][19][20].…”
mentioning
confidence: 99%